An Unusual Case of Acute Abdomen: Ovarian Vein Thrombosis - Ghimire, Asmita; Singh, Meeta; Bista, Kesang Dikki; Ojha, Neebha; Bajracharya, Sunita; Katuwal, Neeta (Journal of Nepal Health Research Council, 2018)
Ovarian vein thrombosis is one of the rare causes for acute abdomen. Occult presentation of this disease may lead to diagnostic dilemma. A sixteen years female who was operated as a case of ectopic pregnancy was finally diagnosed as having ovarian vein thrombosis. She was successfully treated with anticoagulant.